Metode Topsis Untuk Menentukan Karyawan Terbaik - Yuda, Andika Dirma; Widhiarso, Wijang (MDP Student Conference, 2025)
PT. Supra Indolub Perkasa is an official distributor of ExxonMobil Lubricants in Indonesia. Currently, the company faces challenges in the employee evaluation process, which remains conventional, lacks proper documentation, and has limitations in terms of objectivity and accuracy. This process often takes a long time, is prone to data entry errors, and lacks transparency, which can lead to suboptimal decision -making. Therefore, this study aims to develop a Web -Based Decision Support System (DSS) using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method. The system is developed by implementing the RUP (Rational Unified Process) methodology and the Laravel framework to support a more systematic employee data management process. The evaluation criteria include attendance, technical skills, non-technical skills, and personality aspects. The results of the study indicate that this system can improve accuracy, accelerate the evaluation process, and support fair, transparent, and data -driven decision-making. With this system, the company can more easily determine the best employees in an objective manner.